THE IMPACT OF THE RELIABILITY OF THE ACCOUNTING INFORMATION SYSTEM UPON THE BUSINESS PERFORMANCE VIA THE MEDIATING ROLE OF THE QUALITY OF FINANCIAL REPORTING - Al-Dmour, Ahmed (The International Journal of Accounting and Business Society, 2018)
This study aims to examine the relationships of the reliability of the Accounting Information System (AIS) based on the implementation of SysTrust's framework (principles and criteria) as an internal control method to the business performance and the mediating role of the quality of financial reporting in this relationship among Jordanian public listed companies. – Based on the literature review and contingency theory; an integrated conceptual framework was developed to guide this study. The study's conceptual framework consists of three major constructs: the reliability of AIS was conceptualized and measured by the SysTrust's framework (principles and criteria) the business performance was measured by the financial and non-financial indicators and the quality of financial reporting was conceptualized and measured by the IASB's framework fundamental qualitative characteristics. A total of 239 responses were obtained through a self-administered questionnaire from PLCs in the Amman stock market. The empirical findings of the study suggest that the reliability of the AIS is based on the implementation of SysTrust’s framework has a significant and positive relation to business performance and the quality of financial reporting significantly mediate the relationship.